Spatiotemporal Pattern of Doublecortin Expression in the Retina of the Sea Lamprey - Fernández-López, Blanca; Romaus-Sanjurjo, Daniel; Senra-Martínez, Pablo; Anadón, Ramón; Barreiro-Iglesias, Antón; Rodicio, María Celina (Frontiers in Neuroanatomy, 2016)
Despite the importance of doublecortin (DCX) for the development of the nervous system, its expression in the retina of most vertebrates is still unknown. The key phylogenetic position of lampreys, together with their complex life cycle, with a long blind larval stage and an active predator adult stage, makes them an interesting model to study retinal development. Here, we studied the spatiotemporal pattern of expression of DCX in the retina of the sea lamprey. In order to characterize the DCX expressing structures, the expression of acetylated α-tubulin (a neuronal marker) and cytokeratins (glial marker) was also analyzed. Tract-tracing methods were used to label ganglion cells. DCX immunoreactivity appeared initially in photoreceptors, ganglion cells and in fibers of the prolarval retina. In larvae smaller than 100 mm, DCX expression was observed in photoreceptors, in cells located in the inner nuclear and inner plexiform layers and in fibers coursing in the nuclear and inner plexiform layers, and in the optic nerve. In retinas of premetamorphic and metamorphic larvae, DCX immunoreactivity was also observed in radially oriented cells and fibers and in a layer of cells located in the outer part of the inner neuroblastic layer of the lateral retina. Photoreceptors and fibers ending in the outer limitans membrane showed DCX expression in adults. Some retinal pigment epithelium cells were also DCX immunoreactive. Immunofluorescence for α-tubulin in premetamorphic larvae showed coexpression in most of the DCX immunoreactive structures. No cells/fibers were found showing DCX and cytokeratins colocalization. The perikaryon of mature ganglion cells is DCX negative. The expression of DCX in sea lamprey retinas suggests that it could play roles in the migration of cells that differentiate in the metamorphosis, in the establishment of connections of ganglion cells and in the development of photoreceptors. Our results also suggest that the radial glia and retinal pigment epithelium cells of lampreys are neurogenic. Comparison of our observations with those reported in gnathostomes reveals similarities and interesting differences probably due to the peculiar development of the sea lamprey retina.